Pathological description of a non-motor variant of multiple system atrophy. Issue 12 (14th November 2008) - Gaig, C; Iranzo, A; Tolosa, E; Vilaseca, I; Rey, M J; Santamaria, J
Abstract : Multiple system atrophy (MSA) is a neurodegenerative disorder that usually presents clinically as a combination of parkinsonism, cerebellar syndrome and autonomic failure. Patients with MSA can present other clinical features, such as inspiratory stridor and rapid eye movement (REM) sleep behaviour disorder (RBD). We report a patient with pathologically confirmed MSA who presented with a longstanding history of stridor, RBD and autonomic disturbances but did not develop overt parkinsonism or cerebellar signs. This case illustrates that MSA may present clinically without its cardinal motor symptoms, and that stridor and RBD may be clues to recognise the disease in a patient with autonomic failure.